A Systematic Literatur Review: Factors Affecting of Expat Employee Performance - Basuni, Basuni; Churiyah, Madziatul; Zagladi, Arief Noviarakhman (International Journal of Business, Law, and Education, 2024)
This literature research effectively found 10 pertinent studies that were taken from papers that were indexed in Scopus (Q1-Q4) using the PRISMA guidelines. Using the Watase Uake program, this analysis classified the themes and demonstrated how the emergent themes were related to one another. The results of this systematic literature review show that several factors affect their performance, including learning orientation, positive affectivity, boundaryless mindset, trust and organizational support, personality and emotional intelligence and cross-cultural competence which includes cultural intelligence and cultural empathy. In addition to these various factors, it also requires cultural adjustment or expatriates adjustment which can be interpreted as an effort from both parties, namely expatriates and the company concerned in reducing cultural and environmental barriers with pro-active efforts from both. Good adjustment skills are required by an expatriate